Rancang Bangun Jig dan Fixture Produk Oval Handle untuk Proses Milling dengan Sistem Plug and Play - Rafly Bagus Falqi; Bayu Wiro Karuniawan; Fais Hamzah (Proceedings Conference On Design Manufacture Engineering And Its Application, 2022)
The manufacturing industry is an industry where the machining process is done by hand or controlled with the help of machines that can run automatically and with manual supervision. Along with the development of industrial technology, the process of making the same product in large quantities and with precision becomes a requirement in the manufacturing industry. Jigs and fixtures appear as a problem solution for these conditions, but other problems arise from the use of jigs and fixtures. Tool changes and loading and unloading times cannot be utilized properly which can have a long-lasting adverse effect on manufacturing industry companies. There is a solution that helps to fix this problem, namely by updating the jig and fixture design using the Ulrich method, three jig designs and oval handle fixtures will be made using a plug and play system. Calculation of the cutting force received by the workpiece against the vise grip force to ensure the jig and fixture can hold the oval handle well. The results of the jig and fixture design research using the Ulrich method will be selected based on the highest value and safe cutting force calculations.